(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Corruption concept testifies to its imperfection and weakness and arises from the "bowels" of the state, the low legal culture of not only officials, but also society as a whole. After all, officials are a part of society. At the same time, corruption is one of the elements of the "legal" shadow life.